Evolution of the U.S. Republican Party’s Foreign Policy Platform and Its Implementation Challenges (2000–2004) - K. K. Sukhoverkhov (Vestnik MGIMO-Universiteta)
American politics is shaped by numerous variables that influence the development of both domestic and foreign policy. Among these, the formulation of party platforms plays a critical role in determining the policy direction of U.S. administrations. While it is often assumed that party platforms diverge from actual policy outcomes, recent research suggests otherwise in the U.S. context. Party platforms serve as official documents articulating a party’s ideological, political, and economic principles, including pre-election promises and foundational stances on various issues for the electoral cycle, typically spanning four years. This article examines the process of party platform formulation, focusing on the Republican Party's platform in 2000 and its subsequent implementation.During the 1990s, the Republican Party initiated a reformation of its platform following a series of electoral defeats in presidential races. This restructuring, led by figures such as George W. Bush and shaped by influential conservative think tanks, embraced a strategy known as "compassionate conservatism." However, the actual trajectory of U.S. administrations often diverges from the initial platform due to unforeseen circumstances. This phenomenon was particularly evident during the presidency of George W. Bush, where foreign policy experienced a significant shift towards neoconservative influences.The events of September 11, 2001, acted as a catalyst, fundamentally reshaping foreign policy objectives and altering public sentiment towards the Bush administration, as highlighted by sociological studies. These developments led to substantial changes in the nation's regional foreign policy priorities, reflecting the dynamic interplay between pre-election platforms and the realities of governance.